2020
DOI: 10.24874/ti.2020.42.01.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molybdenum Disulfide Nano-particles on Dry Sliding Behavior of Carbon Fiber Reinforced Epoxy

Abstract: Carbon fiber reinforced polymers shows a rapidly increasing trend toward the replacement process of conventional materials by composites at numerous field applications ranging from house appliances to huge industries, because of its good mechanical, thermal and chemical properties. Carbon Reinforced epoxy composites recommended as an engineering material for a lot of tribological applications. In the present work molybdenum disulfide (MoS2) Nano-particles were used as filling material for enhancing wear resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…126,127 As observed by Chin and Yousif, the presence of kenaf fibers in the compound reduces the epoxy coefficient from 0.75 to 0.56. 128 It has been reported that a decline in friction coefficient was attained with the use of coir, betelnut, and palm oil as reinforcement materials by approximately 30%, 46%, and 60%, respectively. This is due to a shift in the counterpart's worn path and composite surfaces, that is, the role of the change in roughness when film transfer is produced in opposite regions.…”
Section: Tribological Performancementioning
confidence: 99%
“…126,127 As observed by Chin and Yousif, the presence of kenaf fibers in the compound reduces the epoxy coefficient from 0.75 to 0.56. 128 It has been reported that a decline in friction coefficient was attained with the use of coir, betelnut, and palm oil as reinforcement materials by approximately 30%, 46%, and 60%, respectively. This is due to a shift in the counterpart's worn path and composite surfaces, that is, the role of the change in roughness when film transfer is produced in opposite regions.…”
Section: Tribological Performancementioning
confidence: 99%
“…Because of its environmental friendliness impact, natural fibers, fillers and other additives like date palm seed, mango dry leaves orange peel wastes were proposed as tribological performance enhancer as well as improving mechanical behavior of polymer composites [1][2][3][4]. It was concluded that friction coefficient of carbone fiber-reinforced epoxy remarkably decreases by means of using molybdenumdisulfied nano powder [5], nanocarbon [6] as tribological performance modifier filler and to improve wear resistance. Mechanical properties, stiffness and hardness improved in epoxy composites by addition of natural fillers as walnut shell, hazelnut shell, and sunflower husk [7].…”
Section: Introductionmentioning
confidence: 99%